Cover. Issue 2 (6th February 2020) - Teng, Fei; Wei, Lingfei; Yu, Dedong; Deng, Liquan; Zheng, Yuanna; Lin, Haiyan; Liu, Yuelian
Abstract : The cover image is based on the Original Article Vertical bone augmentation with simultaneous implantation using deproteinized bovine bone block functionalized with a slow delivery of BMP‐2 by Yuelian Liu et al., https://doi.org/10.1111/clr.13558 .